Against the hounds of hell: a life of Howard Thurman - Eisenstadt, Peter R. (The American South series, 2021)
"A biography of the American theologian and educator Howard Thurman. Thurman was a prominent African American civil rights leader who influenced many in his work for social justice, including Dr. Martin Luther King Jr"--